Transitioning Bryan: The Transition to Adulthood and the Medical Home - Holly Gooding; Caitlin O'Reilly; Elissa Weitzman; Pamela Burke; Adrianne Goncalves; Sarah Pitts (Association of American Medical Colleges, 2015)
Abstract Introduction For the one in five adolescents with a special healthcare need, the transition from pediatric to adult-centered health care can be particularly challenging. In 2011, the American Academy of Pediatrics, American Academy of Family Physicians, and the American College of Physicians published guidelines for the transition of all youth to adult-centered health care and provided additional guidance for youth with special healthcare needs. Key to this process is the frequent and regular assessment of youth's readiness to transition to an adult model of care. This evolving case allows multidisciplinary learners to develop skills in the assessment, treatment, and management of youth transitioning from the pediatric to the adult medical home with an emphasis on the role of the multidisciplinary team. Methods During the administration of this resource, learners review the case of Bryan, a 15-year-old male patient newly diagnosed with Type 1 diabetes. The case is presented over three 75− to 120-minute-long sessions. During this time learners review and discuss the case. Provided probing questions may be used to facilitate discussion. Results Learners reported on standard pre− and postcase 4-point Likert-type scales (1 = not at all confident, 4 = very confident) that the case experience improved their ability to: (1) counsel adolescents transitioning into adulthood (precase M = 3.0, postcase M = 3.6), (2) devise a tailored transition plan (precase M = 2, postcase M = 3.4), and (3) identify age− and developmental stage-appropriate resources (precase M = 2, postcase M = 3.2). Learners also reported that the case experience improved their understanding of the role of a medical doctor, nurse practitioner, nutritionist, psychologist, and social worker in the care of adolescents transitioning into young adulthood. Discussion We find learners are typically surprised that the transition to adulthood is a scholarly field within both medicine and psychology. Learners enjoy reflecting on their personal transition to adulthood (or that of their children, depending on their age), and this brings richness to the case. One element we included in the second year was a question-and-answer session with a young adult with Type 1 diabetes to learn about about her personal experience transitioning to adulthood. If similar patient educators or volunteers are available at the local institution, this could be included at any point in the case.